2017
DOI: 10.3389/fevo.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Light at Night Reduces Daily Energy Expenditure in Breeding Great Tits (Parus major)

Abstract: The ecological impact of artificial light at night (ALAN) is an increasingly recognized process that accompanies expanding urbanization. Yet, we have limited knowledge on the impact of ALAN on wild species, and on the potential to mitigate any negative effects by using different light sources and colors. In birds, effects of ALAN on activity levels are reported for several species and, hence, their daily energy expenditure (DEE) may be affected. DEE is a potent mediator of life-history trade-offs and fitness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 72 publications
1
72
4
Order By: Relevance
“…For example, applying a shorter than optimal cutoff rule would lead to an exponential increase of overrated visits, because individuals that stay longer at the nest than the used cutoff are counted twice (Lendvai et al, 2015). That happens in 90.0% of all visits when a cutoff of 6 s (blue tits; García-Navas et al, 2009) is applied to our video data, and 58.2% of all visits when a cutoff of 17 sec (great tits; Welbers et al, 2017) is used. These cited studies divided the processed registrations by two to calculate individual visit rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, applying a shorter than optimal cutoff rule would lead to an exponential increase of overrated visits, because individuals that stay longer at the nest than the used cutoff are counted twice (Lendvai et al, 2015). That happens in 90.0% of all visits when a cutoff of 6 s (blue tits; García-Navas et al, 2009) is applied to our video data, and 58.2% of all visits when a cutoff of 17 sec (great tits; Welbers et al, 2017) is used. These cited studies divided the processed registrations by two to calculate individual visit rates.…”
Section: Discussionmentioning
confidence: 99%
“…This arbitrary decision is based on the assumptions that the cutoff time is shorter than both the expected time spent outside (c.f., refractory period; Johnstone et al, 2014) and inside the nest and may have large implications for parameter accuracy (see Discussion). For example, earlier studies with passerine birds applied a cutoff of 6 s (blue tits: García-Navas, Ortego, & Sanz, 2009;Johnsen, Delhey, Schlicht, Peters, & Kempenaers, 2005) or 17 s (great tits, Parus major: Welbers et al, 2017). The remaining records were then divided by two to reach a visit rate for the given period.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published caterpillar abundance and phenology data from our study sites (Welbers et al. ). While we have shown that green and white light strongly increased the availability of caterpillars, we have detected no effect of any light color on the timing of the spring caterpillar peak.…”
Section: Discussionmentioning
confidence: 99%
“…, Welbers et al. ). Similarly, annual changes in photoperiod modulate seasonal reproduction, molt, migration, immune function, and metabolic rate (Gwinner , Nelson and Demas , Bradshaw and Holzapfel , Hut , Helm et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation